2008
DOI: 10.5380/avs.v13i1.11555
|View full text |Cite
|
Sign up to set email alerts
|

Impacto Da Idade Ao Parto No Desempenho Produtivo E Reprodutivo Em Vacas Holandesas Primíparas

Abstract: impacto da idade ao parto no desempenHo produtivo e reprodutivo em vacas Holandesas primÍparas (Impact of age at calving on lactation and reproduction performance at the first-parity holsteins)GreboGi, a.¹; ostrensKY, a.¹; poHl, f.¹; almeida, r.²; Weiss, r.r.²; KoZicKi, l.e.¹; breda J.c.³; Giacomeli a.m.³ ¹Pontifícia Universidade Católica do Paraná ²Universidade Federal do Paraná ³Acadêmicos do Curso de Medicina Veterinária da PUCPR RESUMO -Com o objetivo de determinar o impacto da idade ao primeiro parto (IPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…The average calving interval was approximately 14 months (Table 2), similar to the reported by Zafar et al (2008) and Grebogi et al (2008), who found 14.3 and 13 months, respectively, in Holstein cows. According to Bahonar et al (2009) a period of 12 to 13 months, can be considered optimal for dairy cows.…”
Section: Resultssupporting
confidence: 88%
“…The average calving interval was approximately 14 months (Table 2), similar to the reported by Zafar et al (2008) and Grebogi et al (2008), who found 14.3 and 13 months, respectively, in Holstein cows. According to Bahonar et al (2009) a period of 12 to 13 months, can be considered optimal for dairy cows.…”
Section: Resultssupporting
confidence: 88%
“…The values found for IP and PS were higher than those reported by other researchers. Grebogi et al (2008) and Almeida et al (2017) found mean values of 390 and 110, and 420 and 61 days, for IP and PS respectively. However, they were like those found by Marestone et al (2013), who reported mean values of 449 (±118.2) and 178 (±118.73) days for Holstein cows in the states of São Paulo and Paraná, respectively.…”
Section: Table 5 Effect Of the Season On The Productivity And Milk Comentioning
confidence: 94%